PENGARUH MOTIVASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT CITRA MANDIRI DISTRIBUSINDO - Noviardi, Doddy; purba, Daris (LPPM Universitas Putera Batam, 2021)
For an organization or agency, human resources are referred to as the main factor he driving force of the organization Whatever the goals of the organization, the organization must be formed based on various visions. The purpose of this research is to find out how the influence of motivation, and compensation simultaneously on the performance of employees of PT. Citra Mandiri Distribusindo. This study uses the saturation method sampling technique because the population is not large, namely 110 employees. That the number of population and samples in saturated sampling is the same. Data analysis is carried out using multiple linear regression analysis while testing the hypothesis in this studyn using the t test and the F test using the SPSS version 26 software program. From the results Hypothesis testing is known that the motivation variable at PT Citra Mandiri Distribusindo has a significant effect on compensation Variables at PTCitra Mandiri Distribusindo has a significant effect, motivation and compensation together The variable at PT Citra Mandiri Distribusindo has a significant effect,